Control of water flow rate in ACB-HVAC systems - Govindasamy Praveen Kumar (2015)
Active Chilled Beam (ACB) type Heating, Ventilation and Air Conditioning (HVAC) systems has grown a great deal of interest and attention in the past decade. ACBs are favoured by consumers when they plan to implement a HVAC system. Its tremendous scope is due to the inherent benefits that it offers such as cost savings, less maintenance, Energy Savings and reduced Building Space Requirements. This thesis discusses on implementing a suitable control for controlling the water flow rate in ACBs. Automatic System Identification is designed and implemented to reduce engineer's time in designing a controller apt for the system. Modelling of the system, design of controller, tuning and implementation is done in a LabVIEW program. A comparison between designed PID and Fuzzy controller is discussed in detail in this report.